299 IMPROVEMENT IN EXERCISE CAPACITY IN OVERWEIGHT CHILDREN TREATED IN A LIFESTYLE MODIFICATION PROGRAM. Issue 1 (1st January 2007) - Mayman, G. A.; Evans, W. N.; Acherman, R. J.; Cass, K. A.; Kip, K. T.; Luna, C. F.; Rothman, A.; Coviello, L.; Restrepo, H.
Abstract : Background: Physical inactivity and decreased exercise capacity have been associated with long-term poor prognosis in terms of morbidity and mortality in overweight children. Objectives: To assess changes in exercise capacity in overweight children attending a 12-week lifestyle modification program. Methods: This study includes data from 121 children with body mass index (BMI) ≥ 95th percentile who complete a 12-week lifestyle modification program. The program consists of nutrition counseling and medically supervised exercise. BMIs were assessed using the 2000 CDC growth charts. Exercise capacity was estimated by the amount of exercise load (Rockport walking test) and the energy cost of exercise (metabolic equivalents [METs]). All measurements were taken at entry and at the end of the program. Each individual served as his or her own control. Results: The group was composed of 50 girls and 73 boys, mean age 11.2 years (range 6-17 years) and ethnic distribution of Hispanic, 43%; Caucasian, 33%; African American, 7%; and other races, 13%. By the end of the program there was significant increase in the Rockport test (19.5 ± 11.9 vs 29.2 ± 9.3, p < .001) and METs (3.0 ± 0.6 vs 3.5 ± 0.5, p < .001). There was also a significant decrease in BMI Z -score (2.4 ± 0.3 vs 2.3 ± 0.3, p < .001). Conclusions: This group of children was successful in achieving a significant improvement in their exercise capacity and BMI Z -score, after participation in a 12-week lifestyle modification program.